RANCANG BANGUN SISTEM MONITORING PENYIRAMAN OTOMATIS GREENHOUSE BERBASIS IOT DENGAN WEB SERVER - Muhamad Ilham; Onny Setyawati; Raden Arief Setyawan (Jurnal Mahasiswa TEUB, 2022)
Greenhouse can be made according to the conditions of the season for certain plants as expected, namely by adjusting the amount of soil moisture and temperature. The methodology used in regulating soil temperature and humidity is to make an automatic greenhouse watering device with a web server. To detect temperature using DHT22 and soil moisture using a capacitive sensor v1.2. For actuator, it uses two pumps, namely a water pump and a mist pump. So that the sensor and actuator output can be monitored and stored properly, a monitoring system for temperature and soil moisture in the greenhouse is designed using MQTT communication. Data from the controller node will be processed and sent using an ESP32 microcontroller connected by wifi to the Thingsboard server using MQTT communication. In this system, the web werver delay test, data usage, and testing monitor sensor values and monitoractuator conditions are carried out. From the data from the web server delay test results and the data usage that has been tested, the system takes 2-3 seconds in a single data transfer to the Thingsboard server and data usage in one month requires 386MB of internet data. While testing the sensor values and actuator conditions, the system is able to provide real-time responses and is stored on the Thingsboard server as a monitoring tool in the greenhouse. Keywords: Greenhouse, web server, monitoring